We can't hear you : enhancing stakeholder engagement through effective meeting practices : a thesis presented in partial fulfilment of the requirements for the degree of Master of Management in Communication Management at Massey University, Palmerston North, New Zealand - Whitehouse, Danette-Ann (Massey University, 2010)
With increasing governmental pressure on tertiary institutions to seek feedback from external stakeholders, it is timely to review how effective this interaction is in relation to programme development. This research investigates the stakeholder advisory committee meetings operating at Universal College of Learning (UCOL), Palmerston North/New Zealand, to determine if they are an effective method of engaging with industry stakeholders. Knowledge about the meeting practices of the stakeholder advisory committees is deficient, but despite this, UCOL continues to utilise the meetings as the main method of engagement with industry. A literature review was completed to consider the issues that are important when managing stakeholder engagement, along with a review of the theoretical approaches to meeting management. In addition, a questionnaire was supplied to staff and industry representatives from a sample of the stakeholder advisory committees, and an interview was then completed by members from a sub-section of these committees. The research determined that both industry representatives and UCOL representatives on the committees were not satisfied with various aspects of the stakeholder advisory committee meetings. Issues of concern included a lack of clarity around the meeting purpose, poor attendance, confusion over the frequency of meetings, a lack of contact and feedback between meetings, and a lack of opportunity for industry representatives to provide input during the meetings. Potential solutions to the issues raised include ensuring that a purpose statement is created by each committee and communicated to all members. Ensuring regular contact takes place between meetings to ensure members are reminded of meetings, in both written and verbal form, and to check that contact information remains current, will improve attendance at advisory committee meetings. Opportunities for members to connect with each other outside of meetings also need to be provided to encourage engagement. Overall, the emphasis for the meetings needs to be focused on the industry representatives with all elements designed to meet their needs, so as to enable UCOL to collect the industry feedback required to support programme development.
Keywords: Universal College of Learning; UCOL; Meeting management; Stakeholder advisory; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management